Handbook of molecular and cellular methods in biology and medicine - Cseke, Leland J. (Boca Raton : CRC Press/Taylor & Francis Group, 2012)
"Reflecting the milestones in the field that have occurred since the publication of the first edition, this book provides an updated tool k it that incorporates conventional as well as modern approaches to tackl ing biological and medicinal research in the post genomic era. The auth ors have evaluated, revised, and sometimes replaced all protocols with more efficient, reliable, or simpler ones. The book is also completely reorganized and covers topics of modern "omics" approaches, including g enomics, proteomics, and metabolomics. This is followed coverage of the Manipulation of Biological Systems, including RNAi, and the use of mic roscopy"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Molecular biology -- Laboratory manuals; Cytological Techniques -- Laboratory Manuals